Composite molecular sieve catalyst, preparation method thereof and application of composite molecular sieve catalyst in reaction for preparing low-carbon olefin through direct catalytic cracking of waste plastics

By using composite molecular sieve catalysts, including SSZ-13 molecular sieve, spherical ultra-large pore mesoporous molecular sieve and metal oxides, the preparation of low-carbon olefins is directly catalyzed for the cracking of waste plastics, solving the problem of low-carbon olefin content in the existing technology, and achieving efficient and economical chemical raw materials production.

CN119819359AActive Publication Date: 2025-04-15CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311308010.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-10
Publication Date
2025-04-15
Estimated Expiration
2043-10-10

AI Technical Summary

Technical Problem

In the prior art, the content of low-carbon olefins recovered in the chemical recycling and utilization of waste plastics is relatively small, making it difficult to effectively produce pure and high-quality low-carbon olefins.

Method used

Low-carbon olefins are directly prepared by using composite molecular sieve catalysts, including SSZ-13 molecular sieve, spherical ultra-large pore mesoporous molecular sieve and metal oxides.

Benefits of technology

It has achieved efficient conversion of waste plastics into low-carbon olefins, solved the problem of waste plastic recycling, and increased the production of important chemical raw materials, which has good economic benefits and environmental protection effects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819359A_ABST
    Figure CN119819359A_ABST
Patent Text Reader

Abstract

The invention relates to the field of catalysts and the field of high polymer material recycling, and discloses a composite molecular sieve catalyst, a preparation method thereof and application of the composite molecular sieve catalyst in a reaction for preparing low-carbon olefin through direct catalytic cracking of waste plastics. The composite molecular sieve catalyst comprises an SSZ-13 molecular sieve, a sphere-like super-macroporous mesoporous molecular sieve and a metal oxide, wherein the specific surface area of the sphere-like super-macroporous mesoporous molecular sieve is 300-500m < 2 > / g, the pore volume is 0.9-2.2 ml / g, and the pore diameter is 9-16nm; based on the total weight of the composite molecular sieve catalyst, the content of the SSZ-13 molecular sieve is 33.5-61.5 wt%, the content of the sphere-like super-macroporous mesoporous molecular sieve is 38-63 wt%, and the content of the metal oxide is 0.5-3.5 wt%. By adopting the composite molecular sieve catalyst disclosed by the invention, the problem of recycling the waste plastics is solved, and the yield of the important chemical raw material low-carbon olefin is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of catalysts and polymer material recycling, and in particular to a composite molecular sieve catalyst and a preparation method thereof, as well as an application in the direct catalytic cracking of waste plastics to produce light olefins. Background Art

[0002] Since the advent of plastic products in the 20th century, they have been widely used in various fields around the world with the characteristics of light weight, high strength, corrosion resistance, good chemical stability, easy processing, and beautiful and practical. However, plastics are difficult to degrade naturally. Although conventional landfill technology requires little investment and is simple to operate, it will occupy a large amount of land and cause land pollution. Although incineration technology can achieve the reduction requirements and recover some energy at the same time, this process is prone to release a large amount of hydrocarbons, nitrides, sulfides and highly toxic substances, which directly threaten human and ecological health. Therefore, the recycling and high-value utilization of waste plastics as a measure to save energy and protect the environment has been widely valued by countries around the world. The methods for recycling and utilizing waste plastics mainly include classified recycling, preparation of monomer raw materials, production of clean fuel and use for power generation.

[0003] Large-scale waste plastic recycling enterprises that operate in a standardized manner will gradually further refine the recycled waste plastics, continue to develop and apply new technologies and new products for waste plastics, gradually expand the application areas of waste plastics, and increase the added value of recycled plastic products. In the existing technology, the chemical recycling scheme for waste plastics is mainly waste plastic cracking technology. There are three basic methods for waste plastic cracking, namely: thermal cracking (one-stage method), catalytic cracking (one-stage method) and thermal cracking-catalytic modification (two-stage method). The earliest developed waste plastic cracking technology is thermal cracking technology. This technology refers to a thermal conversion process in which a thermochemical decomposition reaction occurs under high temperature and anaerobic conditions to convert large molecular weight organic matter in waste plastic products into small molecular weight liquids, fuel gas, coke and other substances. The reaction temperature of this process is generally controlled at 350-900℃. If a catalyst is added during the thermal cracking process, it is catalytic thermal cracking technology, which can not only reduce the cracking temperature, but also improve product performance. The thermal cracking-catalytic reforming method is an improvement on the catalytic cracking method. After the waste plastics are thermally cracked, the cracking gas is catalytically reformed with a catalyst. This method produces higher quality products than the thermal cracking and catalytic cracking methods, is more flexible to operate, and has lower operating costs, but the process is more complicated.

[0004] Cracking technology has wide flexibility in treating waste plastics and good energy recovery, and is one of the waste plastic treatment technologies with broad application prospects. In the prior art, the products produced by the one-step thermal cracking method and the one-step catalytic cracking method are mainly fuel oil, and only a small amount of low-carbon olefins (ethylene, propylene, butene) can be obtained. If a large amount of low-carbon olefins are required, a two-stage method of thermal cracking-catalytic modification is required. Therefore, exploring a new chemical recovery process to produce pure and high-quality final products is an important research direction for plastic waste treatment. Summary of the invention

[0005] The purpose of the present invention is to provide a composite molecular sieve catalyst and its preparation method as well as its application in the direct catalytic cracking of waste plastics to produce light olefins in view of the current situation that the content of light olefins recovered in the chemical recycling of waste plastics is low. The composite molecular sieve catalyst of the present invention not only solves the recycling problem of waste plastics, but also increases the production of light olefins, an important chemical raw material.

[0006] In order to achieve the above object, the present invention provides a composite molecular sieve catalyst in the first aspect, wherein the composite molecular sieve catalyst comprises SSZ-13 molecular sieve, spherical ultra-large pore mesoporous molecular sieve and metal oxide, wherein the specific surface area of ​​the spherical ultra-large pore mesoporous molecular sieve is 300-500m 2 / g, the pore volume is 0.9-2.2ml / g, and the pore diameter is 9-16nm; and based on the total weight of the composite molecular sieve catalyst, the content of the SSZ-13 molecular sieve is 33.5-61.5% by weight, the content of the spherical ultra-large pore mesoporous molecular sieve is 38-63% by weight, and the content of the metal oxide is 0.5-3.5% by weight.

[0007] The second aspect of the present invention provides a method for preparing the aforementioned composite molecular sieve catalyst, wherein the preparation method comprises:

[0008] (1) Mixing SSZ-13 molecular sieve and metal oxide precursor aqueous solution and contacting and reacting them; then removing water and drying to obtain microporous molecular sieve dry powder.

[0009] (2) The microporous molecular sieve dry powder and the spherical ultra-large pore mesoporous molecular sieve raw powder are mixed and ball-milled, and then calcined to obtain a composite molecular sieve catalyst.

[0010] The third aspect of the present invention provides an application of the aforementioned composite molecular sieve catalyst in the direct catalytic cracking of waste plastics to produce light olefins, wherein the application comprises: contacting the waste plastics with a catalyst for reaction, wherein the catalyst is the aforementioned composite molecular sieve catalyst.

[0011] Through the above technical solution, the technical solution of the present invention has the following advantages:

[0012] 1. The composite molecular sieve catalyst provided by the present invention has a stable structure and good high temperature resistance, and can ensure stability under long-term high temperature conditions in the catalytic cracking reaction of waste plastics.

[0013] 2. The composite molecular sieve catalyst provided by the present invention includes SSZ-13 molecular sieve with certain surface acidity, spherical ultra-large pore mesoporous molecular sieve with larger pore size and metal oxides for adjusting surface acidity and electron distribution. The chemical structure of the catalyst is conducive to the cracking of waste plastic polymers and the generation of target products, and the pore structure of the catalyst is conducive to the diffusion of raw material and product molecules during the reaction process.

[0014] 3. The composite molecular sieve catalyst provided by the present invention can convert waste plastics into low-carbon olefins in one step when used for direct catalytic cracking of waste plastics to produce low-carbon olefins, which is a new method for chemical recycling of waste plastics. It not only solves the problem of recycling waste plastics, but also increases the production of important chemical raw materials, low-carbon olefins, and has good economic benefits.

[0015] 4. When the composite molecular sieve catalyst provided by the present invention is used for the direct catalytic cracking of waste plastics to produce light olefins, the process conditions are mild, the operation is easy, and the requirements for the reaction device are not high.

[0016] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings:

[0018] Figure 1 is a small-angle X-ray diffraction (XRD) spectrum of the quasi-spherical ultra-large pore mesoporous molecular sieve A prepared in Example 1;

[0019] Figure 2 is a scanning electron microscope image (SEM) of the spherical ultra-large pore mesoporous molecular sieve A prepared in Example 1;

[0020] Figure 3 is a wide-angle X-ray diffraction (XRD) spectrum of the composite molecular sieve catalyst A of Example 1;

[0021] Figure 4 This is the pore size distribution diagram of the composite molecular sieve catalyst A of Example 1. DETAILED DESCRIPTION

[0022] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0023] As mentioned above, the first aspect of the present invention provides a composite molecular sieve catalyst, wherein the composite molecular sieve catalyst comprises SSZ-13 molecular sieve, spherical ultra-large pore mesoporous molecular sieve and metal oxide, wherein the specific surface area of ​​the spherical ultra-large pore mesoporous molecular sieve is 300-500m 2 / g, the pore volume is 0.9-2.2ml / g, and the pore diameter is 9-16nm; and based on the total weight of the composite molecular sieve catalyst, the content of the SSZ-13 molecular sieve is 33.5-61.5% by weight, the content of the spherical ultra-large pore mesoporous molecular sieve is 38-63% by weight, and the content of the metal oxide is 0.5-3.5% by weight.

[0024] The inventor of the present invention has found that in the prior art, there is no process for directly catalytically cracking waste plastics to produce low-carbon olefins (including ethylene, propylene, and butene). The purpose of the present invention is to solve this problem. According to the inventor's understanding of the physical and chemical properties of heterogeneous catalysts, the catalyst used for catalytic cracking of waste plastics to directly prepare low-carbon olefins should have a certain acidity and good hydrothermal stability. Based on the above requirements, the SSZ-13 molecular sieve, which has a stable skeleton structure and a certain acidity, is very suitable as the main component of the waste plastic cracking catalyst. The SSZ-13 molecular sieve has a chabazite (CHA) structure, which is composed of AlO4 and SiO4 tetrahedrons connected end to end through oxygen atoms, and orderly arranged into an ellipsoidal cage (0.73nm×1.2nm) with an octahedral ring structure and a three-dimensional cross-channel structure. Although the SSZ-13 molecular sieve has a regular structure and good skeleton symmetry, the size of the three-dimensional cross-channel is small (the pore size is 0.38nm×0.38nm). Waste plastics are polymer products with a large molecular weight and a relatively long molecular chain. In the cracking reaction of waste plastic products, it is difficult for the larger reactant molecules and product molecules to diffuse in the narrow channels, which not only affects the contact between the reactants and the active centers, but also easily leads to the occurrence of side reactions such as deep dehydrogenation, which in turn leads to the decline of catalyst performance. Compared with SSZ-13 molecular sieve, the spherical super-large pore mesoporous molecular sieve has larger pore size (9-16nm) and larger pore volume (up to 1cm 3 / g or more), which is very suitable for catalytic reactions involving macromolecules. However, the spherical super-large pore mesoporous molecular sieve is a full silicon material with extremely weak surface acidity, which is not suitable for catalyzing the cracking reaction of waste plastics alone as a catalyst. The inventors of the present invention found in the development and research of waste plastic cracking catalysts that if the structural advantages of all-silicon mesoporous inorganic materials and the surface acidic centers of zeolite molecular sieves are comprehensively utilized, a certain amount of spherical super-large pore mesoporous molecular sieves are mixed with SSZ-13 molecular sieves, the specific surface area and pore volume of the catalyst can be effectively increased, and the internal diffusion performance in the reaction can be significantly improved. In addition, the surface acidity and electron distribution of the cracking catalyst are appropriately adjusted using metal oxides, which can effectively promote the cracking reaction and the generation of target products. The composite molecular sieve catalyst comprising SSZ-13 molecular sieve, spherical super-large pore mesoporous molecular sieve and metal oxide at the same time, when used as a cracking catalyst for the catalytic conversion reaction of waste plastics, can not only effectively improve the activity of the cracking catalyst, but also increase the selectivity of light olefins.

[0025] According to the present invention, preferably, based on the total weight of the composite molecular sieve catalyst, the content of the SSZ-13 molecular sieve is 37.5-56.5% by weight, the content of the spherical super-large pore mesoporous molecular sieve is 42.5-59.5% by weight, and the content of the metal oxide is 1-3% by weight. More preferably, based on the total weight of the composite molecular sieve catalyst, the content of the SSZ-13 molecular sieve is 42.5-51.5% by weight, the content of the spherical super-large pore mesoporous molecular sieve is 47-55% by weight, and the content of the metal oxide is 1.5-2.5% by weight. In the present invention, the use of the above-mentioned specific contents of each component can make the prepared composite molecular sieve catalyst have better catalytic activity and higher selectivity for light olefins when used for direct catalytic cracking of waste plastics to prepare light olefins.

[0026] According to the present invention, the SiO2 / Al2O3 molar ratio of the SSZ-13 molecular sieve is 10-40. Preferably, the SiO2 / Al2O3 molar ratio of the SSZ-13 molecular sieve is 20-30. The SSZ-13 molecular sieve can be obtained commercially. In the present invention, specifically, the SSZ-13 molecular sieve is more preferably: a SSZ-13 molecular sieve with a SiO2 / Al2O3 molar ratio of 20 purchased from Nanjing Jicang Nano Technology Co., Ltd.; a SSZ-13 molecular sieve with a SiO2 / Al2O3 molar ratio of 30 purchased from Zhuoran Environmental Protection Technology (Dalian) Co., Ltd.

[0027] According to the present invention, the metal oxide is selected from one or more of alkaline earth metal oxides and transition metal oxides; preferably, the alkaline earth metal oxide is selected from one or more of magnesium oxide, calcium oxide, strontium oxide and barium oxide; preferably, the transition metal oxide is zinc oxide. In the present invention, the specific metal oxide selected from the present invention has the advantage of improving the surface acidity and surface electron distribution of the cracking catalyst, making the catalyst surface characteristics more suitable for the waste plastic cracking reaction.

[0028] According to the present invention, the specific surface area of ​​the spherical ultra-large pore mesoporous molecular sieve is 320-450m 2 / g, the pore volume is 1.2-1.8ml / g, and the pore diameter is 11-14nm.

[0029] According to the present invention, the method for preparing the spherical ultra-large pore mesoporous molecular sieve raw powder comprises:

[0030] (1) in the presence of a template and water, a silicon source, an acid, ammonium fluoride and heptane are mixed and contacted, and the mixture obtained after the mixed contact is crystallized, filtered, washed and dried in sequence to obtain a spherical mesoporous material raw powder;

[0031] (2) The spherical mesoporous material raw powder is subjected to a template removal treatment, a primary heat activation treatment and a secondary heat activation treatment in sequence to obtain a spherical ultra-large pore mesoporous molecular sieve.

[0032] According to the present invention, in the method for preparing spherical ultra-large pore mesoporous molecular sieve raw powder, in step (1), the silicon source can be tetraethyl orthosilicate, methyl orthosilicate, propyl orthosilicate, sodium orthosilicate and silica sol, preferably tetraethyl orthosilicate.

[0033] According to the present invention, in the method for preparing spherical ultra-large pore mesoporous molecular sieve raw powder, in step (1), the acid agent can be a conventional substance in the art that can provide acidic conditions, such as hydrochloric acid, sulfuric acid, etc., preferably hydrochloric acid.

[0034] According to the present invention, in the method for preparing spherical ultra-large pore mesoporous molecular sieve raw powder, in step (1), the heptane refers to a straight-chain or branched alkane with 7 carbon atoms, preferably n-heptane.

[0035] According to the present invention, in the preparation method of quasi-spherical ultra-large pore mesoporous molecular sieve raw powder, in step (1), the template is a triblock copolymer of polyoxyethylene-polyoxypropylene-polyoxyethylene EO20PO70EO20. The template can be purchased commercially (for example, it can be purchased from Aldrich Company, the trade name is P123, the molecular formula is EO20PO70EO20), and can also be prepared by various existing methods.

[0036] According to the present invention, the method for preparing spherical ultra-large pore mesoporous molecular sieve raw powder, in step (1), the molar ratio of the template, the silicon source, the acid, the ammonium fluoride and the heptane is 1: (2-500): (100-2000): (0.7-200): (20-1650). Furthermore, the molar ratio of the template, the silicon source, the acid, the ammonium fluoride and the heptane is 1: (10-250): (200-500): (1-180): (50-1450).

[0037] According to the present invention, in the preparation method of spherical ultra-large pore mesoporous molecular sieve raw powder, in step (1), the mixed contact method includes: stirring for more than 4 minutes at a temperature of 25-60°C, and then standing for more than 1 hour. In order to be more conducive to the uniform mixing of various substances, according to a preferred embodiment of the present invention, the mixed contact is carried out under stirring conditions. Preferably, the mixed contact method includes: stirring for 10-240 minutes at a temperature of 25-60°C, and then standing for 4-24 hours.

[0038] According to the present invention, in the preparation method of spherical ultra-large pore mesoporous molecular sieve raw powder, in step (1), the crystallization conditions include: crystallization temperature of 90-180°C, crystallization time of 10-40h. Preferably, the crystallization temperature is 95-105°C, and the crystallization time is 20-36h.

[0039] According to the present invention, in the preparation method of spherical ultra-large pore mesoporous molecular sieve raw powder, in step (1), there is no special requirement for the filtering method, which can be a filtering method known in the art, including gravity filtration, pressure filtration, vacuum filtration or centrifugal filtration. Preferably, the filtering process specifically includes: using a suction bottle, vacuuming the bottom side of the funnel or filtering using a centrifugal filter.

[0040] According to the present invention, in the preparation method of spherical ultra-large pore mesoporous molecular sieve raw powder, in step (1), the washing conditions are not particularly limited. For example, the washing process may include: obtaining a solid product after filtration, repeatedly washing the solid product with distilled water (the number of washing times can be 2-10) and then filtering.

[0041] According to the present invention, the method for preparing spherical ultra-large pore mesoporous molecular sieve raw powder, in step (1), the drying process can be carried out in a drying oven, and the drying conditions may include: a temperature of 60-150°C and a time of 2-30h; under preferred conditions, the drying conditions include: a temperature of 70-110°C and a time of 6-20h.

[0042] According to the present invention, in the preparation method of the spherical ultra-large pore mesoporous molecular sieve raw powder, in step (2), the template release agent treatment includes: calcining the spherical mesoporous material raw powder at 300-600° C. in a static air atmosphere for 8-50 hours. Preferably, the template release agent treatment conditions include: temperature of 400-500° C., time of 16-30 hours.

[0043] According to the present invention, in the preparation method of spherical ultra-large pore mesoporous molecular sieve raw powder, in step (2), the thermal activation treatment is carried out in an inert atmosphere, and after the first thermal activation treatment, the temperature is lowered to room temperature and then the temperature is continued to be raised for a second thermal activation treatment. According to the present invention, the conditions of the first thermal activation treatment include: in an inert atmosphere, the treatment temperature is 25-800°C, preferably 25-600°C; the treatment time is 3-48h, preferably 36-48h.

[0044] According to the present invention, in the preparation method of spherical ultra-large pore mesoporous molecular sieve raw powder, in step (2), the conditions of the secondary thermal activation treatment include: in an inert atmosphere, the treatment temperature is 25-800°C, preferably 25-600°C; the treatment time is 3-48h, preferably 36-48h; more preferably, the treatment conditions of the primary thermal activation treatment are the same as the treatment conditions of the secondary thermal activation treatment.

[0045] In a preferred embodiment of the present invention, the conditions of the thermal activation treatment include: in a nitrogen atmosphere, at 10 m 3 / s to 15m 3 / s flow rate of nitrogen, from room temperature to 250 ℃ at 0.5-10 ℃ per minute, and stay for 1-10 hours, then increase the temperature to 500-600 ℃ at 0.5-10 ℃ per minute, keep the temperature for 2-10 hours, and then return to room temperature; secondary thermal activation treatment, in nitrogen atmosphere, at 10m 3 / s to 15m 3 / s flow rate of nitrogen, from room temperature to 250 ° C at 0.5-10 ° C per minute, and stay for 1-10 hours, then 0.5-10 ° C per minute to 400-800 ° C and keep warm for 2-10 hours, and then cool to room temperature to obtain a spherical ultra-large pore mesoporous molecular sieve. Through thermal activation treatment, the structure of the material can be made more stable. The spherical mesoporous molecular sieve after thermal activation is used to prepare a waste plastic cracking catalyst, which can make the catalyst structure stable during the reaction process.

[0046] According to the present invention, the pore size of the composite molecular sieve catalyst is bimodal, the micropore size is 0.3-0.5 nm, and the mesopore size is 9-16 nm.

[0047] According to the present invention, the specific surface area of ​​the composite molecular sieve catalyst is 410-480m2 / g, pore volume is 0.7-1.1ml / g; preferably, the specific surface area of ​​the composite molecular sieve catalyst is 420-470m 2 / g, and a pore volume of 0.75-1 ml / g; more preferably, the specific surface area of ​​the composite molecular sieve catalyst is 435-455 m 2 / g, and the pore volume is 0.81-0.95ml / g.

[0048] The second aspect of the present invention provides a method for preparing the aforementioned composite molecular sieve catalyst, wherein the preparation method comprises:

[0049] (1) mixing SSZ-13 molecular sieve and a metal oxide precursor aqueous solution and contacting and reacting them; then removing water and drying them to obtain a microporous molecular sieve dry powder;

[0050] (2) The microporous molecular sieve dry powder and the spherical ultra-large pore mesoporous molecular sieve raw powder are mixed and ball-milled, and then calcined to obtain a composite molecular sieve catalyst.

[0051] According to the present invention, in step (1), the aqueous solution of the metal oxide precursor comprises a metal salt and water; the metal salt is selected from one or more water-soluble salts of alkaline earth metals and transition metals, preferably one or more nitrates of magnesium, calcium, strontium, barium and zinc;

[0052] According to the present invention, in step (1), the mass concentration of the metal oxide precursor aqueous solution is 0.1-3%, preferably 0.2-2%.

[0053] According to the present invention, in step (1), the weight ratio of the SSZ-13 molecular sieve to the metal oxide precursor aqueous solution is 1:(3-30), preferably 1:(5-20).

[0054] According to the present invention, in step (1), the contact reaction conditions include: temperature of 10-100° C., preferably 30-80° C.; time of 0.5-50 h, preferably 2-20 h. Preferably, in order to achieve a better mixing effect, the SSZ-13 molecular sieve and the metal oxide precursor aqueous solution can be mixed by rapid stirring or ultrasonic means to improve the mixing efficiency.

[0055] According to the present invention, in step (1), the dehydration method is not particularly limited and can be a dehydration method known in the art, such as: dehydration by evaporation using a rotary evaporator, or dehydration by heating and stirring.

[0056] According to the present invention, in step (1), the drying conditions include: temperature of 60-150° C., preferably 80-130° C.; time of 1-30 h, preferably 3-20 h.

[0057] According to the present invention, in step (2), the weight ratio of the microporous molecular sieve dry powder to the spherical ultra-large pore mesoporous molecular sieve raw powder is 1:(0.5-2), preferably 1:(0.7-1.5).

[0058] According to the present invention, in step (2), the ball milling is carried out in a ball mill, wherein the diameter of the grinding balls in the ball mill can be 2-3 mm; the number of grinding balls can be reasonably selected according to the size of the ball mill jar, and for a ball mill jar of 100-300 mL, 2-8 grinding balls can usually be used; the material of the grinding balls is agate or polytetrafluoroethylene, preferably agate. The conditions of the ball milling include: the rotation speed of the grinding balls can be 200-600r / min, preferably 300-500r / min; the temperature in the ball mill jar can be 30-90°C, preferably 40-80°C; the ball milling time can be 5-50h, preferably 8-24h.

[0059] According to the present invention, in step (2), the calcination conditions include: a temperature of 450-650° C., preferably 500-600° C.; and a calcination time of 5-40 h, preferably 8-20 h.

[0060] The third aspect of the present invention provides an application of a composite molecular sieve catalyst in the direct catalytic cracking of waste plastics to produce light olefins, wherein the application method of the catalyst comprises: under specific conditions, contacting waste plastic powder or particles with the composite molecular sieve catalyst for reaction.

[0061] According to the present invention, the conditions for contacting the waste plastic powder or particles with the composite molecular sieve catalyst include: the contact temperature can be 420-580°C, preferably 450-540°C; the contact pressure can be 0.01-1Mpa, preferably 0.05-0.5Mpa; the contact time can be 0.5-12h, preferably 1-5h; the weight ratio of the composite molecular sieve catalyst to the waste plastic powder or particles can be 1:0.5-50, preferably 1:2-30.

[0062] The present invention will be described in detail below through examples.

[0063] In the following examples and comparative examples:

[0064] The small-angle XRD test of the sample was carried out on a D8 ADVANCE high-power rotating target X-ray diffractometer produced by BRUKER AXS of Germany, with a scanning range of 0.5-10°.

[0065] The wide-angle XRD test of the sample was carried out on an X'Pert MPD X-ray powder diffractometer of Philips Company in the Netherlands, with a Cu Kα target and a scanning range of 2θ=5-90°.

[0066] The pore structure parameter analysis of the samples was carried out on an ASAP2020-M+C adsorption instrument purchased from Micromeritics, Inc., USA. The samples were vacuum degassed at 350°C for 4 hours before measurement, and the specific surface area of ​​the samples was calculated using the BET method, and the pore volume was calculated using the BJH model.

[0067] The scanning electron microscope images of the samples were obtained using an XL-30 field emission environmental scanning electron microscope produced by FEI Company in the United States.

[0068] The elemental analysis experiment of the samples was carried out on an EagleⅢ energy dispersive X-ray fluorescence spectrometer produced by EDAX, USA.

[0069] The drying oven was produced by Shanghai Yiheng Scientific Instrument Co., Ltd., model DHG-9030A.

[0070] The muffle furnace is produced by CARBOLITE, model CWF1100.

[0071] The triblock copolymer polyoxyethylene-polyoxyisobutylene-polyoxyethylene EO used in the examples and comparative examples 20 PO 70 EO 20 It is a product purchased from Aldrich Company with the trade name of P123, and the average molecular weight is 5800. SSZ-13 molecular sieve with SiO2 / Al2O3 molar ratio of 20 was purchased from Nanjing Jicang Nano Technology Co., Ltd.; SSZ-13 molecular sieve with SiO2 / Al2O3 molar ratio of 30 was purchased from Zhuoran Environmental Protection Technology (Dalian) Co., Ltd. All other reagents used in the examples and comparative examples were purchased from Sinopharm Chemical Reagent Co., Ltd., and the reagent purity was analytical grade.

[0072] Example 1

[0073] (1) Preparation of spherical ultra-large pore mesoporous molecular sieves

[0074] Add 2.4 g of P123 and 0.028 g of ammonium fluoride to 80 mL of 1.75 mol / L hydrochloric acid solution, and stir at 20°C until P123 and ammonium fluoride are completely dissolved. Then add 17 mL of n-heptane and 5.5 mL of tetraethyl orthosilicate to the above solution, stir vigorously at 20°C for 4 minutes and let stand for 1 hour. Transfer the resulting solution to a polytetrafluoroethylene-lined reactor and crystallize at 100°C for 24 hours. Wash the solid obtained after filtration with distilled water 8 times and dry at 110°C for 6 hours to obtain spherical ultra-large pore mesoporous molecular sieve raw powder.

[0075] The spherical ultra-large pore mesoporous molecular sieve powder was calcined at 500°C for 24 hours to remove the template. Then, nitrogen was introduced (nitrogen flow rate was 13m3 / s), the temperature was raised from room temperature to 250°C at 1°C per minute, and kept for 2 hours, then raised to 550°C at 1°C per minute, kept for 8 hours, and then cooled to room temperature. Using exactly the same conditions, the thermal activation treatment was repeated once to obtain a spherical ultra-large pore mesoporous material A.

[0076] The specific surface area of ​​spherical ultra-large pore mesoporous molecular sieve A is 350m 2 / g, pore volume 1.5cm 3 / g, average pore size 12nm.

[0077] Figure 1 This is the low-angle XRD spectrum of spherical ultra-large pore mesoporous molecular sieve A. Figure 1 It is shown that the sample has three clearly visible diffraction peaks at small angles below 2°, proving that the mesoporous material in the catalyst has a typical two-dimensional hexagonal mesoporous channel structure.

[0078] Figure 2 This is a scanning electron microscope (SEM) image of the spherical ultra-large pore mesoporous material A. From the SEM image, it can be seen that the molecular sieve has a spherical morphology and a particle diameter of 2.2 μm.

[0079] (2) Preparation of composite molecular sieve catalyst

[0080] 6.1 g of magnesium nitrate hexahydrate was dissolved in 500 g of distilled water to prepare an aqueous solution. 46 g of SSZ-13 molecular sieve (SiO2 / Al2O3=30) was added to the above magnesium nitrate aqueous solution, stirred at 60°C for 5 h, and then the water was removed using a rotary evaporator. The solid product was dried at 110°C for 8 h to obtain microporous molecular sieve dry powder A.

[0081] The above-mentioned microporous molecular sieve dry powder A and 52g of spherical ultra-large pore mesoporous molecular sieve A were added to a 300ml ball mill, and 6 agate grinding balls with a diameter of 2mm were placed to start ball milling. The temperature in the ball mill was controlled at 50°C, the speed of the grinding balls was 400r / min, and the ball milling time was 10h. The powder obtained after ball milling was calcined at 550°C for 16h to obtain a composite molecular sieve catalyst A.

[0082] Based on the total weight of the catalyst A, the content of the SSZ-13 molecular sieve was 46.2% by weight, the content of the spherical ultra-large pore mesoporous molecular sieve A was 51.9% by weight, and the content of magnesium oxide was 1.9% by weight.

[0083] The specific surface area of ​​catalyst A is 446 m 2 / g, pore volume 0.92cm 3 / g.

[0084] Small angle XRD spectrum of catalyst A and Figure 1Three clearly visible diffraction peaks appeared on the spectrum. This shows that the spherical ultra-large pore mesoporous molecular sieve still has a relatively regular mesoporous channel structure after being prepared into a cracking catalyst, and the catalyst preparation process does not destroy the basic structure of the mesoporous molecular sieve.

[0085] Figure 3 This is the wide-angle XRD spectrum of catalyst A. Figure 3 It is shown that the wide-angle x-ray diffraction angles of the sample are mainly: 2θ = 9.5°, 14.1°, 16.2°, 17.9°, 20.7°, 25.0° and 30.7°. The above diffraction signals are consistent with the CHA structure diffraction spectrum of SSZ-13 molecular sieve, indicating that the crystal phase of SSZ-13 molecular sieve has not changed significantly during the preparation of the catalyst and still maintains a good skeleton structure. In addition, there is no diffraction signal corresponding to the metal oxide in the wide-angle XRD spectrum, indicating that the metal oxide component is uniformly dispersed on the catalyst and the particle size is less than 2nm.

[0086] Figure 4 is the pore size distribution diagram of catalyst A. Figure 4 The above shows that the sample has an obvious double-pore structure, with double pore diameters of 0.4nm and 12nm respectively. The pore with a diameter of 0.4nm is provided by the SSZ-13 molecular sieve, and the pore with a diameter of 12nm is provided by the spherical ultra-large pore mesoporous molecular sieve.

[0087] (3) Evaluation of the reaction performance of direct conversion of waste plastics to light olefins

[0088] The performance of the catalyst in the catalytic cracking reaction of waste plastics was evaluated in a fixed bed reactor. The catalyst loading was 10 g, the loading of waste polyethylene plastic particles was 50 g, the reaction temperature was 520 ° C, the reaction pressure was 0.1 MPa, the reaction time was 1 hour, and after the product was cooled and the gas-liquid was separated, the gas composition was analyzed by an Agilent 6890 gas chromatograph equipped with an Al2O3-S capillary column and a hydrogen flame detector (FID), and the quantitative analysis was performed using a programmed temperature and a correction factor; the liquid composition was analyzed by an Agilent 7890A gas chromatograph equipped with a PONA column. The reaction results are shown in Table 1.

[0089] Example 2

[0090] (1) Preparation of spherical ultra-large pore mesoporous molecular sieves

[0091] Add 3 grams of P123 and 0.036 grams of ammonium fluoride to 100 mL of 1.75 mol / L hydrochloric acid solution, and stir at 40°C until P123 and ammonium fluoride are completely dissolved. Then add 25 mL of n-heptane and 8 mL of tetraethyl orthosilicate to the above solution, stir vigorously at 40°C for 10 minutes and let stand for 1 hour. Transfer the resulting solution to a polytetrafluoroethylene-lined reactor and crystallize at 100°C for 24 hours. Wash the solid obtained after filtration with distilled water 6 times and dry at 70°C for 20 hours to obtain spherical ultra-large pore mesoporous molecular sieve raw powder.

[0092] The spherical ultra-large pore mesoporous molecular sieve powder was calcined at 500°C for 24 hours to remove the template. 3 / s), the temperature was raised from room temperature to 250°C at 1°C per minute, and kept for 2 hours, then raised to 500°C at 1°C per minute, and kept for 16 hours, and then cooled to room temperature. Using exactly the same conditions, the thermal activation treatment was repeated once to obtain spherical ultra-large pore mesoporous material B.

[0093] The specific surface area of ​​spherical ultra-large pore mesoporous molecular sieve B is 337m 2 / g, pore volume 1.4cm 3 / g, average pore size 11nm.

[0094] (2) Preparation of composite molecular sieve catalyst

[0095] 2.6 g of strontium nitrate was dissolved in 600 g of distilled water to prepare an aqueous solution. 42 g of SSZ-13 molecular sieve (SiO2 / Al2O3=20) was added to the above strontium nitrate aqueous solution, stirred at 80°C for 2 h, and then the water was removed using a rotary evaporator. The solid product was dried at 130°C for 3 h to obtain microporous molecular sieve dry powder B.

[0096] The above-mentioned microporous molecular sieve dry powder B and 54g of spherical ultra-large pore mesoporous molecular sieve B were added to a 300ml ball mill, and 8 agate grinding balls with a diameter of 2mm were placed to start ball milling. The temperature in the ball mill was controlled at 80°C, the speed of the grinding balls was 500r / min, and the ball milling time was 8h. The powder obtained after ball milling was calcined at 600°C for 8h to obtain composite molecular sieve catalyst B.

[0097] Based on the total weight of the catalyst B, the content of the SSZ-13 molecular sieve is 42.5% by weight, the content of the spherical ultra-large pore mesoporous molecular sieve B is 55% by weight, and the content of strontium oxide is 2.5% by weight.

[0098] The specific surface area of ​​catalyst B is 435m 2 / g, pore volume 0.95cm 3 / g, and the double pore diameters are 0.4nm and 11nm respectively.

[0099] (3) Evaluation of the reaction performance of direct conversion of waste plastics to light olefins

[0100] The reaction performance of Catalyst B was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (3) of Example 1. The evaluation results are listed in Table 1.

[0101] Example 3

[0102] (1) Preparation of spherical ultra-large pore mesoporous molecular sieves

[0103] According to the method of step (1) of Example 1, a spherical ultra-large pore mesoporous molecular sieve A was prepared.

[0104] (2) Preparation of composite molecular sieve catalyst

[0105] 2.2 g of calcium nitrate was dissolved in 400 g of distilled water to prepare an aqueous solution. 52 g of SSZ-13 molecular sieve (SiO2 / Al2O3=30) was added to the above calcium nitrate aqueous solution, stirred at 30°C for 20 h, and then the water was removed using a rotary evaporator. The solid product was dried at 80°C for 20 h to obtain microporous molecular sieve dry powder C.

[0106] The above-mentioned microporous molecular sieve dry powder C and 47g of quasi-spherical ultra-large pore mesoporous molecular sieve A were added into a 300ml ball mill, and 4 agate grinding balls with a diameter of 2mm were placed to start ball milling. The temperature in the ball mill was controlled at 40°C, the speed of the grinding balls was 300r / min, and the ball milling time was 24h. The powder obtained after ball milling was calcined at 500°C for 20h to obtain a composite molecular sieve catalyst C.

[0107] Based on the total weight of the catalyst C, the content of the SSZ-13 molecular sieve is 51.5% by weight, the content of the spherical ultra-large pore mesoporous molecular sieve A is 47% by weight, and the content of calcium oxide is 1.5% by weight.

[0108] The specific surface area of ​​catalyst C is 455m 2 / g, pore volume 0.81cm 3 / g, and the double pore diameters are 0.4nm and 12nm respectively.

[0109] (3) Evaluation of the reaction performance of direct conversion of waste plastics to light olefins

[0110] The reaction performance of Catalyst C was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (3) of Example 1. The evaluation results are listed in Table 1.

[0111] Example 4

[0112] (1) Preparation of spherical ultra-large pore mesoporous molecular sieves

[0113] According to the method of step (1) of Example 1, a spherical ultra-large pore mesoporous molecular sieve A was prepared.

[0114] (2) Preparation of composite molecular sieve catalyst

[0115] 5.4 g of zinc nitrate hexahydrate was dissolved in 700 g of distilled water to prepare an aqueous solution. 38 g of SSZ-13 molecular sieve (SiO2 / Al2O3=20) was added to the above zinc nitrate aqueous solution, stirred at 60°C for 5 h, and then the water was removed using a rotary evaporator. The solid product was dried at 110°C for 8 h to obtain microporous molecular sieve dry powder D.

[0116] The above-mentioned microporous molecular sieve dry powder D and 60g of spherical ultra-large pore mesoporous molecular sieve A were added to a 300ml ball mill, and 6 agate grinding balls with a diameter of 2mm were placed to start ball milling. The temperature in the ball mill was controlled at 50°C, the speed of the grinding balls was 400r / min, and the ball milling time was 10h. The powder obtained after ball milling was calcined at 550°C for 16h to obtain a composite molecular sieve catalyst D.

[0117] Based on the total weight of the catalyst D, the content of the SSZ-13 molecular sieve was 37.5% by weight, the content of the quasi-spherical ultra-large pore mesoporous molecular sieve A was 59.5% by weight, and the content of zinc oxide was 3% by weight.

[0118] The specific surface area of ​​catalyst D is 420 m 2 / g, pore volume 1cm 3 / g, and the double pore diameters are 0.4nm and 12nm respectively.

[0119] (3) Evaluation of the reaction performance of direct conversion of waste plastics to light olefins

[0120] The reaction performance of catalyst D was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (3) of Example 1. The evaluation results are listed in Table 1.

[0121] Example 5

[0122] (1) Preparation of spherical ultra-large pore mesoporous molecular sieves

[0123] According to the method of step (1) in Example 2, a spherical ultra-large pore mesoporous molecular sieve B was prepared.

[0124] (2) Preparation of composite molecular sieve catalyst

[0125] 0.9 g of barium nitrate was dissolved in 300 g of distilled water to prepare an aqueous solution. 57 g of SSZ-13 molecular sieve (SiO2 / Al2O3=30) was added to the above barium nitrate aqueous solution, stirred at 80°C for 2 h, and then the water was removed using a rotary evaporator. The solid product was dried at 130°C for 3 h to obtain microporous molecular sieve dry powder E.

[0126] The above-mentioned microporous molecular sieve dry powder E and 43g of spherical ultra-large pore mesoporous molecular sieve B were added to a 300ml ball mill, and 8 agate grinding balls with a diameter of 2mm were placed to start ball milling. The temperature in the ball mill was controlled at 80°C, the speed of the grinding balls was 500r / min, and the ball milling time was 8h. The powder obtained after ball milling was calcined at 600°C for 8h to obtain composite molecular sieve catalyst E.

[0127] Based on the total weight of the catalyst E, the content of the SSZ-13 molecular sieve was 56.5% by weight, the content of the spherical ultra-large pore mesoporous molecular sieve B was 42.5% by weight, and the content of the barium oxide was 1% by weight.

[0128] The specific surface area of ​​catalyst E is 470 m 2 / g, pore volume 0.75cm 3 / g, and the double pore diameters are 0.4nm and 11nm respectively.

[0129] (3) Evaluation of the reaction performance of direct conversion of waste plastics to light olefins

[0130] The reaction performance of Catalyst E was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (3) of Example 1. The evaluation results are listed in Table 1.

[0131] Example 6

[0132] (1) Preparation of spherical ultra-large pore mesoporous molecular sieves

[0133] According to the method of step (1) of Example 1, a spherical ultra-large pore mesoporous molecular sieve A was prepared.

[0134] (2) Preparation of composite molecular sieve catalyst

[0135] 11 g of magnesium nitrate hexahydrate was dissolved in 400 g of distilled water to prepare an aqueous solution. 33 g of SSZ-13 molecular sieve (SiO2 / Al2O3=20) was added to the above magnesium nitrate aqueous solution, stirred at 60°C for 5 h, and then the water was removed using a rotary evaporator. The solid product was dried at 110°C for 8 h to obtain microporous molecular sieve dry powder F.

[0136] The above-mentioned microporous molecular sieve dry powder F and 63g of quasi-spherical ultra-large pore mesoporous molecular sieve A were added to a 300ml ball mill, and 6 agate grinding balls with a diameter of 2mm were placed to start ball milling. The temperature in the ball mill was controlled at 50°C, the speed of the grinding balls was 400r / min, and the ball milling time was 10h. The powder obtained after ball milling was calcined at 550°C for 16h to obtain a composite molecular sieve catalyst F.

[0137] Based on the total weight of the catalyst F, the content of the SSZ-13 molecular sieve was 33.5% by weight, the content of the spherical ultra-large pore mesoporous molecular sieve A was 63% by weight, and the content of magnesium oxide was 3.5% by weight.

[0138] The specific surface area of ​​catalyst F is 410 m 2 / g, pore volume 1.10cm 3 / g, and the double pore diameters are 0.4nm and 12nm respectively.

[0139] (3) Evaluation of the reaction performance of direct conversion of waste plastics to light olefins

[0140] The reaction performance of Catalyst F was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (3) of Example 1. The evaluation results are listed in Table 1.

[0141] Example 7

[0142] (1) Preparation of spherical ultra-large pore mesoporous molecular sieves

[0143] According to the method of step (1) in Example 2, a spherical ultra-large pore mesoporous molecular sieve B was prepared.

[0144] (2) Preparation of composite molecular sieve catalyst

[0145] 0.9 g of zinc nitrate hexahydrate was dissolved in 600 g of distilled water to prepare an aqueous solution. 62 g of SSZ-13 molecular sieve (SiO2 / Al2O3=30) was added to the above zinc nitrate aqueous solution, stirred at 80°C for 2 h, and then the water was removed using a rotary evaporator. The solid product was dried at 130°C for 3 h to obtain microporous molecular sieve dry powder G.

[0146] The above-mentioned microporous molecular sieve dry powder G and 38g of quasi-spherical ultra-large pore mesoporous molecular sieve B were added to a 300ml ball mill, and 8 agate grinding balls with a diameter of 2mm were placed to start ball milling. The temperature in the ball mill was controlled at 80°C, the speed of the grinding balls was 500r / min, and the ball milling time was 8h. The powder obtained after ball milling was calcined at 600°C for 8h to obtain the composite molecular sieve catalyst G.

[0147] Based on the total weight of the catalyst G, the content of the SSZ-13 molecular sieve was 61.5% by weight, the content of the spherical ultra-large pore mesoporous molecular sieve B was 38% by weight, and the content of zinc oxide was 0.5% by weight.

[0148] The specific surface area of ​​catalyst G is 630 m 2 / g, pore volume 0.50cm 3 / g, and the double pore diameters are 0.4nm and 11nm respectively.

[0149] (3) Evaluation of the reaction performance of direct conversion of waste plastics to light olefins

[0150] The reaction performance of Catalyst G was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (3) of Example 1. The evaluation results are listed in Table 1.

[0151] Comparative Example 1

[0152] (1) Preparation of spherical ultra-large pore mesoporous molecular sieves

[0153] According to the method of step (1) in Example 1, a spherical ultra-large pore mesoporous molecular sieve A was prepared.

[0154] (2) Preparation of composite molecular sieve catalyst

[0155] 14g SSZ-13 molecular sieve (SiO2 / Al2O3=20) and 86g quasi-spherical ultra-large pore mesoporous molecular sieve A were added to a 300ml ball mill, and 6 agate grinding balls with a diameter of 2mm were placed to start ball milling. The temperature in the ball mill was controlled at 50°C, the speed of the grinding balls was 400r / min, and the ball milling time was 10h. The powder obtained after ball milling was calcined at 550°C for 16h to obtain the composite molecular sieve catalyst D1.

[0156] Based on the total weight of the catalyst D1, the content of the SSZ-13 molecular sieve was 14% by weight, and the content of the spherical ultra-large pore mesoporous molecular sieve A was 86% by weight.

[0157] The specific surface area of ​​catalyst D1 is 381m 2 / g, pore volume 1.30cm 3 / g, and the double pore diameters are 0.4nm and 12nm respectively.

[0158] The reaction performance of catalyst D1 was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (3) of Example 1. The evaluation results are listed in Table 1.

[0159] Comparative Example 2

[0160] (1) Preparation of spherical ultra-large pore mesoporous molecular sieves

[0161] According to the method of step (1) in Example 2, a spherical ultra-large pore mesoporous molecular sieve B was prepared.

[0162] (2) Preparation of composite molecular sieve catalyst

[0163] 7.3 g of strontium nitrate was dissolved in 230 g of distilled water to prepare an aqueous solution. 83 g of SSZ-13 molecular sieve (SiO2 / Al2O3=20) was added to the above strontium nitrate aqueous solution, stirred at 80°C for 2 h, and then the water was removed using a rotary evaporator. The solid product was dried at 130°C for 3 h to obtain microporous molecular sieve dry powder D2.

[0164] The above-mentioned microporous molecular sieve dry powder D2 and 10g of spherical ultra-large pore mesoporous molecular sieve B were added to a 300ml ball mill, and 8 agate grinding balls with a diameter of 2mm were placed to start ball milling. The temperature in the ball mill was controlled at 80°C, the speed of the grinding balls was 500r / min, and the ball milling time was 8h. The powder obtained after ball milling was calcined at 600°C for 8h to obtain the composite molecular sieve catalyst D2.

[0165] Based on the total weight of the catalyst D2, the content of the SSZ-13 molecular sieve was 83% by weight, the content of the spherical ultra-large pore mesoporous molecular sieve B was 10% by weight, and the content of strontium oxide was 7% by weight.

[0166] The specific surface area of ​​catalyst D2 is 509m 2 / g, pore volume 0.39cm 3 / g, and the double pore diameters are 0.4nm and 11nm respectively.

[0167] The reaction performance of catalyst D2 was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (3) of Example 1. The evaluation results are listed in Table 1.

[0168] Comparative Example 3

[0169] According to the method of step (1) in Example 1, a spherical ultra-large pore mesoporous molecular sieve A was prepared.

[0170] Eliminate step (2) in Example 1.

[0171] The reaction performance of the quasi-spherical ultra-large pore mesoporous molecular sieve A was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (3) of Example 1. The evaluation results are listed in Table 1.

[0172] Comparative Example 4

[0173] Cancel step (1) in Example 1.

[0174] Catalyst D3 was prepared according to the following steps: 6.4 g of magnesium nitrate hexahydrate was dissolved in 400 g of distilled water to prepare an aqueous solution. 98 g of SSZ-13 molecular sieve (SiO2 / Al2O3=20) was added to the above magnesium nitrate aqueous solution, stirred at 60°C for 5 h, and then the water was removed by a rotary evaporator. The solid product was dried at 110°C for 8 h and calcined at 550°C for 16 h to obtain catalyst D3.

[0175] The specific surface area of ​​catalyst D3 is 561m 2 / g, pore volume 0.29cm 3 / g, and only has micropores with a pore size of 0.4nm.

[0176] The reaction performance of catalyst D3 was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (3) of Example 1. The evaluation results are listed in Table 1.

[0177] Comparative Example 5

[0178] Eliminate step (1) and step (2) in Example 1.

[0179] The reaction performance of SSZ-13 molecular sieve (SiO2 / Al2O3=30) was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (3) of Example 1. The evaluation results are listed in Table 1.

[0180] Comparative Example 6

[0181] According to the method of step (1) in Example 1, a spherical ultra-large pore mesoporous molecular sieve A was prepared.

[0182] The ball milling process in step (2) of Example 1 was eliminated to prepare the composite molecular sieve catalyst D4.

[0183] The reaction performance of catalyst D4 was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (3) of Example 1. The evaluation results are listed in Table 1.

[0184] Comparative Example 7

[0185] Cancel step (1) in Example 1.

[0186] Catalyst D5 was prepared according to the method of step (2) in the embodiment, and the spherical ultra-large pore mesoporous molecular sieve A was replaced with commercially available silicon dioxide powder (specific surface area of ​​274 m 2 / g, pore volume 0.54cm 3 / g), the specific process is as follows:

[0187] 6.1 g of magnesium nitrate hexahydrate was dissolved in 500 g of distilled water to prepare an aqueous solution. 46 g of SSZ-13 molecular sieve (SiO2 / Al2O3=30) was added to the above magnesium nitrate aqueous solution, stirred at 60°C for 5 h, and then the water was removed using a rotary evaporator. The solid product was dried at 110°C for 8 h to obtain microporous molecular sieve dry powder A.

[0188] The above-mentioned microporous molecular sieve dry powder A and 52g of commercially available silicon dioxide powder (specific surface area 274m 2 / g, pore volume 0.54cm 3 / g) was added into a 300ml ball mill, and 6 agate grinding balls with a diameter of 2mm were placed to start ball milling. The temperature in the ball mill was controlled at 50°C, the speed of the grinding balls was 400r / min, and the ball milling time was 10h. The powder obtained after ball milling was calcined at 550°C for 16h to obtain composite catalyst D5.

[0189] The reaction performance of catalyst D5 was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (3) of Example 1. The evaluation results are listed in Table 1.

[0190] Comparative Example 8

[0191] Cancel step (1) in Example 1.

[0192] Catalyst D6 was prepared according to the method of step (2) in the example, except that "52 g of quasi-spherical ultra-large pore mesoporous molecular sieve A" was replaced with "52 g of mesoporous molecular sieve material D".

[0193] The preparation method of mesoporous molecular sieve material D is as follows:

[0194] The template P123 and ammonium fluoride were added to a hydrochloric acid solution with a concentration of 1.75 mol / L, stirred at 20°C until P123 and ammonium fluoride were completely dissolved, and then n-heptane and tetraethyl orthosilicate were added to the above solution. Among them, the molar ratio of P123: tetraethyl orthosilicate: hydrochloric acid: ammonium fluoride: n-heptane is 1:300:90:0.5:18. After vigorous stirring at 20°C for 4 minutes, let it stand for 1 hour. The resulting solution was transferred to a polytetrafluoroethylene-lined reactor and crystallized at 100°C for 24 hours. The solid obtained after filtration was washed 8 times with distilled water and dried at 110°C for 6 hours to obtain the raw mesoporous molecular sieve powder. The raw mesoporous molecular sieve powder was calcined at 500°C for 24 hours to remove the template and obtain the mesoporous molecular sieve material D.

[0195] The specific surface area of ​​mesoporous molecular sieve material D is 276m 2 / g, pore volume 0.7cm 3 / g, and the average pore size is 8nm.

[0196] The reaction performance of catalyst D6 was tested according to the reaction performance evaluation method for direct conversion of waste plastics to light olefins in step (3) of Example 1. The evaluation results are listed in Table 1.

[0197] Table 1

[0198]

[0199] It can be seen from the above results that the composite molecular sieve catalyst provided by the present invention can directly catalyze the conversion of waste plastics into light olefins. The conversion rate of waste plastics is 100%, and the yield of light olefins is high.

[0200] In Comparative Example 1, the content of spherical ultra-large pore mesoporous molecular sieve is too high, the content of SSZ-13 molecular sieve is too low, and the content of metal oxide is not within the scope of the claims. Due to the small number of acidic centers on the catalyst and insufficient activation sites during the reaction, the raw material conversion rate and the yield of light olefins are low.

[0201] In Comparative Example 2, the content of spherical ultra-large pore mesoporous molecular sieve is too low, and the content of SSZ-13 molecular sieve is too high. Due to the small number of macropores in the catalyst, the diffusion of reactants and product molecules is hindered during the reaction, resulting in a low yield of light olefins.

[0202] In Comparative Example 3, only spherical ultra-large pore mesoporous molecular sieve is used as a catalyst. Since the surface acidity of the all-silicon mesoporous molecular sieve is extremely weak, it is not conducive to the high molecular weight cracking reaction of waste plastics, resulting in a low conversion rate and a low yield of light olefins.

[0203] In Comparative Example 4, the catalyst contains only SSZ-13 molecular sieve and metal oxide, and no spherical ultra-large pore mesoporous molecular sieve is added. Since the catalyst contains almost no mesoporous channels, the diffusion of reactant and product molecules during the reaction is severely hindered, resulting in a low yield of light olefins.

[0204] In Comparative Example 5, the catalyst contains only SSZ-13 molecular sieve, and does not contain spherical ultra-large pore mesoporous molecular sieve and metal oxide. Since the catalyst contains almost no mesoporous channels, the diffusion of reactants and product molecules during the reaction is severely hindered, resulting in a low yield of light olefins.

[0205] In Comparative Example 6, the ball milling process was omitted, and the SSZ-13 molecular sieve and the spherical ultra-large pore mesoporous molecular sieve were directly mixed. Since the SSZ-13 molecular sieve with an acidic center and the SBA-3 molecular sieve with a mesoporous structure were not mixed uniformly, the yield of light olefins was low.

[0206] In Comparative Example 7, commercially available silica powder was used to replace the spherical ultra-large pore mesoporous molecular sieve. Since the mesoporous channel structure of the commercially available silica was irregular, the yield of light olefins was low.

[0207] In Comparative Example 8, mesoporous molecular sieve material D is used to replace the spherical ultra-large pore mesoporous molecular sieve. Since the raw material ratio of the mesoporous molecular sieve material D is not within the range specified by the present invention and the thermal activation step is eliminated in the preparation process, the specific surface area, pore volume and average pore diameter of the obtained mesoporous molecular sieve material D are all low, resulting in a low yield of light olefins.

[0208] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A composite molecular sieve catalyst, characterized in that: The composite molecular sieve catalyst comprises SSZ-13 molecular sieve, spherical ultra-large pore mesoporous molecular sieve and metal oxide, wherein the specific surface area of ​​the spherical ultra-large pore mesoporous molecular sieve is 300-500m 2 / g, the pore volume is 0.9-2.2ml / g, and the pore diameter is 9-16nm; and based on the total weight of the composite molecular sieve catalyst, the content of the SSZ-13 molecular sieve is 33.5-61.5% by weight, the content of the spherical ultra-large pore mesoporous molecular sieve is 38-63% by weight, and the content of the metal oxide is 0.5-3.5% by weight.

2. The composite molecular sieve catalyst according to claim 1, wherein Based on the total weight of the composite molecular sieve catalyst, the content of the SSZ-13 molecular sieve is 37.5-56.5% by weight, the content of the spherical ultra-large pore mesoporous molecular sieve is 42.5-59.5% by weight, and the content of the metal oxide is 1-3% by weight; Preferably, based on the total weight of the composite molecular sieve catalyst, the content of the SSZ-13 molecular sieve is 42.5-51.5% by weight, the content of the spherical ultra-large pore mesoporous molecular sieve is 47-55% by weight, and the content of the metal oxide is 1.5-2.5% by weight.

3. The composite molecular sieve catalyst according to claim 1 or 2, wherein: The SiO2 / Al2O3 molar ratio of the SSZ-13 molecular sieve is 10-40.

4. The composite molecular sieve catalyst according to claim 1 or 2, wherein: The metal oxide is selected from alkaline earth metal oxides and / or transition metal oxides; Preferably, the alkaline earth metal oxide is selected from one or more of magnesium oxide, calcium oxide, strontium oxide and barium oxide; Preferably, the transition metal oxide is zinc oxide.

5. The composite molecular sieve catalyst according to claim 1 or 2, wherein: The specific surface area of ​​the spherical ultra-large pore mesoporous molecular sieve is 320-450m 2 / g, the pore volume is 1.2-1.8ml / g, and the pore diameter is 11-14nm.

6. The composite molecular sieve catalyst according to claim 1 or 5, wherein: The preparation method of the spherical ultra-large pore mesoporous molecular sieve raw powder comprises: (1) in the presence of a template and water, a silicon source, an acid, ammonium fluoride and heptane are mixed and contacted, and the mixture obtained after the mixed contact is crystallized, filtered, washed and dried in sequence to obtain a spherical mesoporous material raw powder; (2) The spherical mesoporous material raw powder is subjected to a template removal treatment, a primary heat activation treatment and a secondary heat activation treatment in sequence to obtain a spherical ultra-large pore mesoporous molecular sieve.

7. The composite molecular sieve catalyst according to claim 6, wherein: In step (1), the silicon source is selected from one or more of tetraethyl orthosilicate, methyl orthosilicate, propyl orthosilicate, sodium orthosilicate and silica sol, preferably tetraethyl orthosilicate; and / or, in step (1), the template is a triblock copolymer of polyoxyethylene-polyoxypropylene-polyoxyethylene; and / or, in step (1), the molar ratio of the template, the silicon source, the acid, the ammonium fluoride and the heptane is 1:(2-500):(100-2000):(0.7-200):(20-1650); And / or, in step (2), the conditions of the primary thermal activation treatment and the secondary thermal activation treatment are the same or different, and each includes: in an inert atmosphere, at a temperature of 25-800° C., for a time of 3-48 h; Preferably, the conditions of the primary thermal activation treatment and the secondary thermal activation treatment are the same or different, and each comprises: in a nitrogen atmosphere, 3 / s to 15m 3 / s flow rate of nitrogen, the temperature is raised from room temperature to 250 ° C at 0.5-10 ° C per minute, and kept for 1-10 hours, and then raised to 400-800 ° C at 0.5-10 ° C per minute and kept warm for 2-10 hours.

8. The composite molecular sieve catalyst according to any one of claims 1 to 7, wherein: The pore size of the composite molecular sieve catalyst is bimodal, with a micropore size of 0.3-0.5 nm and a mesopore size of 9-16 nm; And / or, the specific surface area of ​​the composite molecular sieve catalyst is 410-480m 2 / g, pore volume is 0.7-1.1ml / g; Preferably, the specific surface area of ​​the composite molecular sieve catalyst is 420-470m 2 / g, pore volume is 0.75-1ml / g; More preferably, the specific surface area of ​​the composite molecular sieve catalyst is 435-455m 2 / g, and the pore volume is 0.81-0.95ml / g.

9. A method for preparing the composite molecular sieve catalyst according to any one of claims 1 to 8, characterized in that: The preparation method comprises: (1) mixing SSZ-13 molecular sieve and a metal oxide precursor aqueous solution and contacting and reacting them; then removing water and drying them to obtain a microporous molecular sieve dry powder; (2) The microporous molecular sieve dry powder and the spherical ultra-large pore mesoporous molecular sieve raw powder are mixed and ball-milled, and then calcined to obtain a composite molecular sieve catalyst.

10. The preparation method according to claim 9, wherein: The metal oxide precursor aqueous solution comprises a metal salt and water; the metal salt is selected from water-soluble salts of alkaline earth metals and / or transition metals, preferably nitrates of one or more of magnesium, calcium, strontium, barium and zinc; And / or, the mass concentration of the metal oxide precursor aqueous solution is 0.1-3%; and / or, the weight ratio of the SSZ-13 molecular sieve to the metal oxide precursor aqueous solution is 1:(3-30); And / or, the weight ratio of the microporous molecular sieve dry powder to the spherical ultra-large pore mesoporous molecular sieve raw powder is 1:(0.5-2), preferably 1:(0.7-1.5); And / or, the calcination conditions include: temperature of 450-650° C. and time of 5-40 h.

11. Use of the composite molecular sieve catalyst according to any one of claims 1 to 8 in the direct catalytic cracking of waste plastics to produce light olefins, wherein: The application comprises: contacting the waste plastic with a catalyst for reaction, wherein the catalyst is the composite molecular sieve catalyst according to any one of claims 1 to 8.

12. The use according to claim 11, wherein: The contact conditions include: temperature of 420-580°C, pressure of 0.01-1MPa, and contact time of 0.5-12h; And / or, the waste plastic is in powder and / or granular form; And / or, the weight ratio of the composite molecular sieve catalyst to the waste plastic is 1:(0.5-50).

Citation Information

Patent Citations

  • C4 olefin cracking catalyst and preparation method thereof, and catalytic cracking method

    CN111167509A

  • Super-macroporous silica gel-containing catalyst for increasing yield of propylene by light gasoline cracking, and preparation method and application thereof

    CN113546671A

  • Catalyst for preparing propylene and preparation method and application of catalyst

    CN113731477A

  • Processing method and system of waste plastics

    CN114106865A

  • Catalytic cracking catalyst for producing high-yield low-carbon olefins through hydrogenation of LCO as well as preparation method and application of catalytic cracking catalyst

    CN114130426A